FUTURE SPECIALISTS – SPIRITUAL AND PROFESSIONAL EDUCATION OF SECONDARY SCHOOL STUDENTS – A NEED FOR THE DEVELOPMENT OF OUR INDEPENDENT COUNTRY - Zaripova , Gulbahor Kamilovna (Educational Research in Universal Sciences, 2023)
In the article entitled “Future specialists - spiritual and professional education of secondary school students - the need for the development of our independent country,” the author describes the practical implementation of educational reforms in our country, which serves to educate, first of all, an independently thinking person, in conditions of independence, in as a result of which the highest goal of our independent society was scientifically and practically explained in this article, and in this global direction in our country the need arose to educate a person who is perfect in all respects intellectually, morally, aesthetically, spiritually and physically.